An Antibacterial β‐Lactone Kills Mycobacterium tuberculosis by Disrupting Mycolic Acid Biosynthesis. Issue 1 (5th December 2017) - Lehmann, Johannes; Cheng, Tan‐Yun; Aggarwal, Anup; Park, Annie S.; Zeiler, Evelyn; Raju, Ravikiran M.; Akopian, Tatos; Kandror, Olga; Sacchettini, James C.; Moody, D. Branch; Rubin, Eric J.; Sieber, Stephan A.
Abstract: The spread of antibiotic resistance is a major challenge for the treatment of Mycobacterium tuberculosis infections. In addition, the efficacy of drugs is often limited by the restricted permeability of the mycomembrane. Frontline antibiotics inhibit mycomembrane biosynthesis, leading to rapid cell death. Inspired by this mechanism, we exploited β‐lactones as putative mycolic acid mimics to block serine hydrolases involved in their biosynthesis. Among a collection of β‐lactones, we found one hit with potent anti‐mycobacterial and bactericidal activity. Chemical proteomics using an alkynylated probe identified Pks13 and Ag85 serine hydrolases as major targets. Validation through enzyme assays and customized 13 C metabolite profiling showed that both targets are functionally impaired by the β‐lactone. Co‐administration with front‐line antibiotics enhanced the potency against M. tuberculosis by more than 100‐fold, thus demonstrating the therapeutic potential of targeting mycomembrane biosynthesis serine hydrolases. Abstract : Trick and treat : A β‐lactone that acts as an electrophilic mimic of mycolic acid blocks serine hydrolases essential for mycomembrane biosynthesis. Activity‐based protein profiling paired with metabolic labelling studies confirmed the mechanism of action responsible for the potent antibiotic activity of this compound against Mycobacterium tuberculosis .